FACTORS AFFECTING THE EXCHANGE RATE OF FOOD CROPS FARMERS IN NORTH SUMATRA - Perangin-angin, Ratna Amenawati; Sibuea, Muhammad Buhari; Lindawati (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
The agricultural sector has an important role in the national economy and this sector is expected to be one of the supports to improve the welfare of farmers. One indicator that is considered relevant to assess the condition of farmers' welfare is through the Farmer Exchange Rate (NTP). This study aims to Analyze the effect of KUR granting, harvest area, rice production, and GRDP on NTPTP in North Sumatra Province. The data in this study are time series data from 2015 to 2022 analyzed by multiple linear regression. The results showed that the development of NTPTP in North Sumatra Province for the period 2015-2022 experienced an upward and downward trend and tended to increase with an average growth of 3.2%. Rice production experienced an upward and downward trend and tended to decline with an average decrease in production of 4.9%. The rice harvest area experienced an upward and downward trend and tended to decline with an average decrease in harvest area of 4.7%. KUR granting fluctuated over time and increased every year with an average growth of 67.3%. GRDP fluctuates from time to time and increases every year with an average growth of 3.9%. KUR granting, harvest area, rice production, and GRDP simultaneously affect the NTPTP in North Sumatra Province slot deposit 5000. Partially, the provision of KUR and rice production had a positive and significant effect, while the harvest area and GRDP had a negative and significant effect on NTPTP